Propolis as an Anti-allergy Based on Decrease in Total Eosinophil Count in Rat Models - Nambiar, Rashmika; Rohmawaty, Enny; Lismayanti, Leni (Althea Medical Journal, 2015)
Background: Propolis is a natural herb derived from plant resins by bees. Propolis contains flavonoids thatÂ act as anti-allergy. The composition of flavonoids in propolis varies according to each region like Brazilian,Â Chinese, Malaysian and Indonesian propolis due to differences in medicinal plants in that area. The aimÂ of this study is to determine the effect of propolis as an anti-allergy and to determine which is the mostÂ effective among propolis of Brazilian, Malaysian and Indonesian origin.Methods: An experimental study was performed on 28 Wistar male rats divided into four groups, Brazilian,Â Malaysian, Indonesian propolis and a negative control group. The used parameter was decreased in totalÂ eosinophil count in ovalbumin induced allergy in rats. Propolis or aquadest as control were given orallyÂ 0.25ml once daily.Results: All three groups of propolis showed statistically significant results (p<0.05), in decreasing eosinophilÂ count. However, Malaysian and Brazilian propolis showed much more significant effects compared to that ofÂ Indonesian propolis. This could be due to the difference in composition and concentration of flavonoids inÂ Indonesian propolis compared to the Brazilian and Malaysian propolis.Conclusion: Propolis has a significant effect as an anti-allergy. Malaysian and Brazilian propolis are moreÂ effective as an anti-allergy compare to Indonesian propolis. Propolis can thus be used as an alternativeÂ treatment for allergy. [AMJ.2015;2(1):208â12]